Implementasi Metode Pembelajaran Mind Mapping dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran IPS tentang Manusia sebagai Makhluk Sosial di MI Marhatillah Matabe - Ida Laila; Isa Anshori (ISLAMIKA, 2022)
One of the things that need to be considered in carrying out learning and learning activities is learning motivation. If the motivation to learn does not exist in students, then what happens is that students will be less enthusiastic in participating in learning or carrying out learning activities. So, if students lack motivation to learn, educators or parents must play an active role in growing that motivation. The use of less varied methods at MI Mardhatillah Sanalaok Waru Pamekasan, especially in class IV, causes students' boredom and lack of enthusiasm for learning. In this case the teacher requires basic teaching skills in the form of variations in student teaching and the ability to design, implement various strategies or learning methods that are considered suitable for interests and talents and in accordance with the level of student development. Therefore, the lack of student motivation in social studies subjects is due to the approach used by the teacher in the learning process is still teacher centered and the learning methods used are less varied. So there needs to be an explanation of learning methods, one of which is the mind mapping method. In this study there are several problems discussed by the researcher. First, how to apply the mind mapping method. Second, how to increase students' learning motivation through the mind mapping method